Applanation-free femtosecond laser processing of the cornea - Miclea, Manuela (Optical Society of America, 2011)
A novel approach for applanation-free femtosecond refractive surgery with the help of a contact liquid layer is presented. A laboratory device for performing corneal procedures is described based on a femtosecond-laser system which has been tested and evaluated by processing ex vivo pig eyes. With its help, flap cuttings for different flap thicknesses were performed. The accomplished corneal surfaces are comparable to already published results. The reproducibility of the flap thicknesses is very good, with a standard deviation of 10 µm. The processing and removal of an intrastromal lenticule as thin as 30 µm could be shown. The extraction of such lenticule through a corneal side channel could also be accomplished successfully and is a promising improvement of the overall surgery procedure.